Severity and Risk of Death Due to COVID 19 - Shaymaa Hasan Abbas; Rasha Saadi Abbas; Lubab Tarek Nafea (College of Pharmacy / Mustansiriyah University, 2022)
A novel SARS-CoV2 virus appeared since December 2019 and triggering the Corona virus disease (2019-nCoV or COVID-19). Usually the symptoms begin as mild, with only fever, cough, and occasional dyspnea. The severe symptoms such as   pneumonitis, and acute respiratory distress syndrome (ARDS), may occur 5-8 days into COVID-19 illness in a minority of patients. Method:  for this narrative review, more than 25 related scientific articles and reports about COVID- 19 were used from different databases (e.g., PubMed, Google Scholar, and Web of Science) using keywords such as SARS-CoV2, COVID-19, Mortality, and CO-morbidities. Results The results of this review reported that aged people are more vulnerable to severe pattern of COVID-19 disease than people younger than 50 years; probably because of health issues and comorbidities in that population group. Male more than female affected by COVID-19. On the other hand, children might be less probable to infected or might show mild symptoms if infected. The small percentage of current smokers infected with COVID-19 compared with the actual percentage of smokers (50·5%) in China are unlikely to be related with the incidence, severity, or mortality rate of COVID-19. The poorer clinical outcome in COVID-19  infected patients may have related to the presence and number of co morbidities especially hypertension, diabetes and cardiovascular diseases.  The direct SARS-COV2 infection of liver cells might be the cause of liver damage but might be related to other reasons such as systemic inflammation and drug toxicity. The data   suggested that liver damage is more predominant in severe cases especially with pre-existing liver diseases. patients with cancer might be more prone to COVID 19 due to their immunocompromised status but whether or not they have high risk of poor prognoses and sever event not fully established.